P871 Successful detection of dysbiosis and altered short-chain-fatty acids levels in in vitro colonic microbiota culture system using faecal samples of ulcerative colitis. (16th January 2018) - Inoue, J; Sasaki, K; Hoshi, N; Sasaki, D; Kondo, A; Osawa, R
Abstract: Background: Ulcerative colitis (UC) involves chronic and recurring inflammation of the intestinal tract. It is widely recognised that the composition of gut microbiota and intestinal metabolites are altered in UC patients. There is increasing number of clinical studies which supports the idea that imbalance of gut microbiota (dysbiosis) plays a role in pathogenesis and/or progression of UC. We previously reported single–batch fermentation system (Takagi et al ., PLoS One, 2016) which can approximately recapitulate the microbiota of fecal sample in vitro, and could detect the change of microbiota and metabolites when prebiotics were supplemented to the system. It prompted us to test if this system could actually detect the unbalanced fecal microbiota and metabolites of UC patients; which may suggest the potential usefulness of this system for preclinical evaluation of effect of probiotics and prebiotics before administration to patients. Methods: Fecal samples were obtained from 11 UC patients and 13 healthy human subjects (HS). Fecal samples were applied to the single–batch fermentation system and aliquots of fermentation cultures were sampled to analyse the composition of bacteria and short-chain-fatty acids (SCFAs) concentration. Bacterial 16S rRNA gene sequencing was performed with Illumina MiSeq. Concentrations of SCFAs were measured using a high-performance liquid chromatograph. Bacterial component and SCFAs concentration were compared between UC and HS. Results: The bacterial diversity and richness in fecal samples were maintained in corresponding fermentation cultures of both UC and HS. Comparison of principal coordinate plots of the unweighted UniFrac distance showed that compositional difference of microbiota between HS and UC patients were successfully reproduced in the single–batch fermentation system as observed in faces. Relative abundance of family Lachnospiraceae, which includes butyrate producing species, was significantly decreased in the microbiota of UC patients compared with those of HS, which was the same tendency as observed in faces. Butyrate generation was significantly decreased in the colon culture models of UC patients compared with those of HS and strongly correlated with relative abundance of family Lachnospiraceae. Conclusions: In this study, our new culture system could successfully recapitulate the previously shown dysbiosis of reduced family Lachnospiraceae and reduced butyrate level in UC patients in vitro. It may have a potential to be used as an in vitro evaluation system to check the intestinal environment in health and disease. It could be a good model to test whether dysbiosis can be corrected into symbiosis by adding prebiotics and/or probiotics to modify the gut microbiota community in each UC patient.